Follow-up evaluation of the immunological status of children admitted for acute cerebral nervous system infections: a retrospective study - Giulia Spina; Bozzola Elena; Carsetti Rita; Piano Mortari Eva; Cristina Mascolo; Marco Roversi; Villani Alberto (BMC, 2021)
Abstract Background Acute Cerebral Nervous System Infections (ACNS) may cause death or severe complications even to promptly treated children. The role of the immune system in influencing the course and the outcome of meningitis has been studied but it is not yet completely understood. The aim of the research is to ascertain whether children who experienced ACNS infection had a normal immune system. Methods Patients under 18 years of age admitted at Bambino Gesù Children from January 2006 till June 2016 for meningitis were asked to participate to the follow-up study. The immune status was evaluated both clinically and by laboratory investigations. Results Most of the patients over 3 years at follow up had at least one immunological alteration at follow-up evaluation (74%). Considering ACNS infection etiology, certain pathogens were almost exclusive of patients affected by some immunological alteration, regardless of their age. Discussion Our preliminary results indicate that sub-clinical immunological defects may be associated to ACNS pediatric infections. Moreover, to the best of our knowledges, this is the first study correlating pathogens to immune evaluation in ACNS infections. It is, however, important to underline the high frequency of persistent immunological alterations in the analyzed patients. Further studies are needed to confirm our conclusions. Conclusions We recommend an immunological assessment at follow up evaluation in children who experienced an ACNS infection.